Inhibition of Calcineurin/NFAT Signaling Blocks Oncogenic H-Ras Induced Autophagy in Primary Human Keratinocytes - Wang, Shuangshuang; Qian, Hua; Zhang, Liwei; Liu, Panpan; Zhuang, Dexuan; Zhang, Qun; Bai, Fuxiang; Wang, Zhihong; Yan, Yonggan; Guo, Jing; Huang, Jun; Wu, Xunwei (Frontiers in Cell and Developmental Biology, 2021)
Mutations of H-Ras, a member of the RAS family, are preferentially found in cutaneous squamous cell carcinomas. H-Ras has been reported to induce autophagy, which plays an essential role in tissue homeostasis in multiple types of cancer cells and in fibroblasts, however the potential role of H-Ras in regulating autophagy in human keratinocytes has not been reported. In this study, we found that the stable expression of the G12V mutant of H-RAS (H-RasG12V) induced autophagy in human keratinocytes, and interestingly, the induction of autophagy was strongly blocked by inhibiting the calcineurin/NFAT pathway with either a calcineurin inhibitor (Cyclosporin A) or a NFAT inhibitor (VIVIT), or by the siRNA mediated knockdown of calcineurin B1 or NFATc1 in vitro, as well as in vivo. To characterize the role of the calcineurin/NFAT pathway in H-Ras induced autophagy, we found that H-RasG12V promoted the nuclear translocation of NFATc1, an indication of the activation of the calcineurin/NFAT pathway, in human keratinocytes. However, activation of NFATc1 either by the forced expression of NFATc1 or by treatment with phenformin, an AMPK activator, did not increase the formation of autophagy in human keratinocytes. Further study revealed that inhibiting the calcineurin/NFAT pathway actually suppressed H-Ras expression in H-RasG12V overexpressing cells. Finally, CHIP assays showed that NFATc1 potentially binds the promoter region of H-Ras and the binding efficiency was significantly enhanced by the overexpression of H-RasG12V, which was abolished by treatment with the calcineurin/NFAT pathway inhibitors CsA or VIVIT. Taking these data together, the present study demonstrates that the calcineurin/NFAT signaling pathway controls H-Ras expression and interacts with the H-Ras pathway, involving the regulation of H-Ras induced autophagy in human keratinocytes.